Leveraging early HIV diagnosis and treatment in Thailand to conduct HIV cure research - Muccini, Camilla (AIDS Res Ther, 2019)
Thailand has the highest prevalence of HIV among countries in Asia but has also been a pioneer in HIV prevention and treatment efforts in the region, reducing the incidence of new infections significantly over the last two decades. Building upon this remarkable history, Thailand has set an ambitious goal to stop the AIDS epidemic in the country by 2030. A key component of the strategy to achieve this goal includes scale-up of HIV screening programs to facilitate early HIV diagnosis and investment in mechanisms to support immediate initiation of antiretroviral therapy (ART). Initiation of ART during early or acute HIV infection not only reduces viremia, thereby halting onward transmission of HIV, but also may facilitate HIV remission by reducing the size of the latent HIV reservoir and preserving immune function. In Thailand, many efforts have been made to reduce the time from HIV infection to diagnosis and from diagnosis to treatment, especially among men who have sex with men and transgender women. Successfully identifying and initiating ART in individuals with acute HIV infection has been leveraged to conduct groundbreaking studies of novel strategies to achieve HIV remission, including studies of broadly-neutralizing HIV-specific monoclonal antibodies and candidate therapeutic vaccines. These efforts have mostly been deployed in Bangkok and future efforts should include other urban and more rural areas. Continued progress in HIV prevention, screening, and treatment will position Thailand to substantially limit new infections and may pave the way for an HIV cure.